2007
DOI: 10.1002/anie.200700750
|View full text |Cite
|
Sign up to set email alerts
|

IR Spectra of Protonated Carbonic Acid and Its Isomeric H3O+⋅CO2 Complex

Abstract: The authors of this Communication wish to correct a remark in their introductory paragraph: "There have been several unsuccessful attempts to generate and characterize gas-phase H 2 CO 3 by heating solid H 2 CO 3 [3] or NH 4 HCO 3. [12] " This statement is incorrect and misleading, and the authors apologize for their oversight. The sentence should read: "Although there have been several successful attempts to generate and identify gas-phase H 2 CO 3 by heating solid H 2 CO 3 [3] or NH 4 HCO 3 , [12] there is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
22
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…Often, rare gas atoms are used as messengers but small physisorbed molecules like H 2 , N 2 , or even O 2 have also been employed. Major advantages of the messenger technique include enhanced cooling and a substantial reduction of the dissociation energy of the cluster, leading to simpler and colder action spectra achieved with absorption of fewer photons as compared to the bare cluster [3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Often, rare gas atoms are used as messengers but small physisorbed molecules like H 2 , N 2 , or even O 2 have also been employed. Major advantages of the messenger technique include enhanced cooling and a substantial reduction of the dissociation energy of the cluster, leading to simpler and colder action spectra achieved with absorption of fewer photons as compared to the bare cluster [3][4][5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…This sensitive IRPD approach was previously used to elucidate the structure of related fundamental hydrocarbon ions, such as C 2 H 5 + , [11] C 3 H 3 + , [12] C(OH) 3 + , [13] C 6 H 5 + , [14] and C 6 H 7 + . This sensitive IRPD approach was previously used to elucidate the structure of related fundamental hydrocarbon ions, such as C 2 H 5 + , [11] C 3 H 3 + , [12] C(OH) 3 + , [13] C 6 H 5 + , [14] and C 6 H 7 + .…”
mentioning
confidence: 99%
“…Here we report the IR spectrum of isolated C 10 H 16 + in the CH stretching range (s CH ) obtained through He-tagging IR photodissociation (IRPD). This sensitive IRPD approach was previously used to elucidate the structure of related fundamental hydrocarbon ions, such as C 2 H 5 + , [11] C 3 H 3 + , [12] C(OH) 3 + , [13] C 6 H 5 + , [14] and C 6 H 7 + . [15] Weakly bound He or N 2 ligands are attached to C 10 H 16 + to facilitate resonant singlephoton fragmentation, as shown in Figure 3 for C 10 ·He binding energy (D 0 < 1 kJ mol À1 ), [16] the influence of He atoms on the C 10 H 16 + spectrum is very weak and considered negligible.…”
mentioning
confidence: 99%
“…The affording [(UO 2 ) 4 (ZnO)(Ge 2 O 7 ) 2 ] 4– framework is negatively charged, and the remaining positive charge needed to counterbalance the anionic framework is accomplished by protonating of four hydration water molecules within the larger channels. The presence of H 3 O + species was confirmed by FTIR spectroscopy, showing that the O–H stretching and bending vibration bands of UZG‐1 locate at 3536 and 1626 cm –1 , respectively (Figure S1) . Thermogravimetric analysis suggested that the initial weight loss of UZG‐1 from 50 to 110 °C was 3.52 % (Figure S2), corresponding to the departure of four water molecules ( calcd 3.58 %).…”
mentioning
confidence: 87%